A dynamic model describing the effects of soil moisture on mercury speciation and migration in the plow layer. Issue 5 (4th July 2019) - Shi, Daqi; Li, Xingjie; Huang, Yanna; Cui, Xiaqian; Zhang, Zongdi; Li, Dongbo; Yan, Zhenning; Tang, Xueming; Ao, Yansong
ABSTRACT: A dynamic model was constructed to predict the effects of soil water movement on changes and migration of available mercury (Hg) in various layers of different soil types. Various soil types were placed in large boxes. The available Hg content was then determined in vertical layers of the soils. Simultaneously, changes in the equilibrated available Hg content with evaporation were measured. Capillary water absorption was used to maintain the soil water holding capacity. The results were as follows. 1) Soil available Hg migrated upward or downward along with water movement, achieving a stable downward migration rate of 23.5%–35.3% and an upward migration rate of 17.4%–33.3%. The migration rate of available Hg owing to water movement was in the order of sandy loam > loam > clay loam. 2) Under different soil water holding capacities, when migration reached equilibrium, the increase in the amount of bound Hg, which was desorbed into available Hg, was 1.2%–14.3% of the initial available Hg content, and this increase was in the order of sandy loam > loam > clay loam. Based on these findings, a dynamic model describing the effects of soil moisture on Hg speciation and migration in the plow layer was constructed. The model is a true reflection of the impact of variations in soil characteristics (e.g., particle size, organic matter content, pH value, water movement vector, mineral composition, and colloid properties.) with time. This model can provide new insight into the speciation transformation and distribution of Hg. It can also be applied in risk evaluation in remediation of heavy metal contaminated soils.